Defying the Stereotype: Non-Canonical Roles of the Peptide Hormones Guanylin and Uroguanylin - Basu, Nirmalya; Visweswariah, Sandhya S. (Frontiers in Endocrinology, 2011)
The peptide hormones uroguanylin and guanylin have been traditionally thought to be mediators of fluid-ion homeostasis in the vertebrate intestine. They serve as ligands for receptor guanylyl cyclase C (GC-C), and both receptor and ligands are expressed predominantly in the intestine. Ligand binding to GC-C results in increased cGMP production in the cell which governs downstream signaling. In the last decade, a significant amount of research has unraveled novel functions for this class of peptide hormones, in addition to their action as intestinal secretagogues. An additional receptor for uroguanylin, receptor guanylyl cyclase D, has also been identified. Thus, unconventional roles of these peptides in regulating renal filtration, olfaction, reproduction and cell proliferation have begun to be elucidated in detail. These varied effects suggest that these peptide hormones act in an autocrine, paracrine as well as endocrine manner to regulate diverse cellular processes.